Heat-killed Limosilactobacillus reuteri ATCC PTA 6475 prevents bone loss in ovariectomized mice: A preliminary study - Ribeiro, Jaqueline Lemes [UNESP]; Santos, Thaís Aguiar [UNESP]; Garcia, Maíra Terra [UNESP]; Carvalho, Bruna Fernandes do Carmo [UNESP]; Sant’Ana Esteves, Juan Emmanuel Costa; Moraes, Renata Mendonça [UNESP]; Anbinder, Ana Lia [UNESP] (My University, 2024)
Osteoporosis is an important health problem that occurs due to an imbalance between bone formation and resorption. Hormonal deficiency post-menopause is a significant risk factor. The probiotic Limosilactobacillus reuteri has been reported to prevent ovariectomy (Ovx)induced bone loss in mice and reduce bone loss in postmenopausal women. Despite the numerous health benefits of probiotics, as they are live bacteria, the administration is not risk-free for certain groups (e.g., neonates and immunosuppressed patients). We evaluated the effects of L. reuteri (ATCC PTA 6475) and its heat-killed (postbiotic) form on Ovxinduced bone loss. Adult female mice (BALB/c) were randomly divided into four groups: group C—control (sham); group OVX-C—Ovx; group OVX-POS—Ovx + heat-killed probiotic; group OVX-PRO—Ovx + probiotic. L. reuteri or the postbiotic was administered to the groups (1.3x109 CFU/day) by gavage. Bacterial morphology after heat treatment was accessed by scanning electron microscopy (SEM). The treatment started one week after Ovx and lasted 28 days (4 weeks). The animals were euthanized at the end of the treatment period. Bone microarchitecture and ileum Occludin and pro-inflammatory cytokines gene expression were evaluated by computed microtomography and qPCR techniques, respectively. The Ovx groups had lower percentage of bone volume (BV/TV) and number of bone trabeculae as well as greater total porosity compared to the control group. Treatment with live and heat-killed L. reuteri resulted in higher BV/TV and trabecular thickness than the Ovx group. The heat treatment caused some cell surface disruptions, but its structure resembled that of the live probiotic in SEM analysis. There were no statistical differences in Occludin, Il-6 and Tnf-α gene expression. Both viable and heat-killed L. reuteri prevented bone loss on ovariectomized mice, independently of gut Occludin and intestinal Il-6 and Tnf-α gene expression.